Transcription factors and evolution An integral part of gene expression Review. (2020) - MITSIS, THANASIS; EFTHIMIADOU, ASPASIA; BACOPOULOU, FLORA; VLACHAKIS, DIMITRIOS; CHROUSOS, GEORGE P.; ELIOPOULOS, ELIAS
No abstract available